“AMOR EM DIÁLOGO: a contribuição das ciências humanas e da saúde para o cuidado pastoral frente à depressão no contexto pentecostal” - Silva, Cristiane dos Santos Viturino (2021)
This research offers an analysis on the theme of depression within the Assembly of God Madureira Church, where its interpretations were associated with sins, also linked to mental illness, with demonic influences. Its studies and teachings are based on the biblical interpretation that the causes of human suffering are caused by evil spirits, a theological tradition that God is in control of everything. Thus, if something bad happens to one of the church members, it is because this person has practiced a sin, bringing anguish in the soul and reflexes in the body. The goal is to present depression as a phenomenon of “deep sadness” that has undergone advances in theories and was called a disease with biological and psychosocial effects, and also to contribute with an overview of the care, love and compassion of Jesus Christ, and the contribution of the humanities and health to the care of people.